Infrastructure Development and Economic Growth in Java Island:: A Random Effect Panel Data Analysis (2016–2021) - Septriani Septriani; I Gusti Ngurah Oka Widjaya; Risky Angga Pramuja (Econetica: Jurnal Sosial, Ekonomi, dan Bisnis, 2024)
This study aims to examine the impact of infrastructure development and population growth on regional economic growth across six provinces in Java Island from 2016 to 2021. Infrastructure serves as a critical determinant of productivity enhancement and interregional connectivity, while demographic dynamics influence regional production and consumption capacity. The study employs secondary data obtained from Statistics Indonesia (BPS), the Ministry of Finance, and the Ministry of Public Works and Housing (PUPR). A panel data regression approach is applied, comparing the Common Effect Model (CEM), Fixed Effect Model (FEM), and Random Effect Model (REM). Model selection through Chow, Hausman, and Lagrange Multiplier tests identifies the Random Effect Model as the most appropriate specification. The results show that road and electricity infrastructures have a positive and significant effect on Gross Regional Domestic Product (GRDP), whereas population growth has no significant influence on regional economic performance. The coefficient of determination (R²) of 0.8414 indicates that the independent variables collectively explain 84.14 percent of the variation in GRDP. These findings confirm that infrastructure development remains a vital engine of regional economic growth, while population growth must be supported by improvements in human capital and labor productivity to become an effective driver of economic progress. The study contributes to regional development literature and provides policy implications for sustainable and equitable growth planning in Indonesia.